(untitled) (Linguamática, 2020)
This presentation of two prototypes of automatic natural language generation provides an overview of the methodology applied in the description and processing of linguistic data, as well as of the techniques and tools already existing or developed in order to guarantee the functioning of the simulators in German, Spanish and French.